Multivariable Analysis of the Association between Antenatal Depressive Symptomatology and Postpartum Visit Attendance - Shim, Jessica Y.; Stark, Elisabeth L.; Ross, Carolyn M.; Miller, Emily S. (American Journal of Perinatology, 2019)
Objective We sought to evaluate whether antenatal depression was associated with postpartum visit nonattendance.Study Design This retrospective cohort study included women who received prenatal care at the academic outpatient offices of a single tertiary care center between March 1, 2009, and December 31, 2014. Women were screened for antenatal depression using the Patient Health Questionnaire-9. Attendance at the postpartum visit was compared between women with and without antenatal depressive symptomatology using bivariate and multivariable analyses.Results Of the 2,870 women who met the inclusion criteria, 566 (19.7%) did not attend the postpartum visit. Women who did not attend a postpartum visit were younger and more likely to be a racial/ethnic minority, publicly insured, or multiparous; they were more likely to have a higher body mass index, as well as a vaginal delivery. Compared with those without antenatal depressive symptomatology, women with antenatal depressive symptomatology were significantly less likely to attend their postpartum visit (18.6 vs. 29.2%, p < 0.001). This association persisted even after controlling for potential confounders (adjusted odds ratio: 0.69, 95% confidence interval: 0.48–0.99).Conclusion Antenatal depressive symptomatology is significantly associated with nonattendance at the postpartum visit.
Keywords: depression; mental health; mood disorder; perinatal; postpartum visit